Leadership style and personnel performance: A literature review - Fajar, Rheza Kurnia (International research journal of management, IT and social sciences, 2022)
This article mainly discusses the relationship between leadership style and employee performance. Research on the relationship between leadership style and employee performance still shows mixed results. The purpose of this study was to determine the relationship between leadership style and employee performance by comparing the results of primary research on these two variables. The method used is a conceptual analysis of various previous studies in the last ten years. The results show that there is a significant and positive relationship between leadership style and employee performance, especially in the Indonesian context where social relations take priority in society. This implies that managers must be able to create a favorable leadership style to encourage employee performance improvement, although this is not the only thing that must be considered.